When Children’s Literature Transcends its Genre: Translating Alice in Wonderland - Kibbee, Douglas (Meta, 2003)
AbstractA book such as Alice in Wonderland, written for a girl, but nowadays understandable only by adults, the translation of proper nouns can reveal the audience for which translators have addressed their works. This article looks at the translation of proper nouns. These cultural traits are first names, historical references, place names and names of languages: should these be changed to facilitate comprehension by children? This study is then used to evaluate some aspects of theories proposed by Shavit and Oittinen concerning adaptation and translation.